2000
DOI: 10.1002/1521-3773(20001215)39:24<4588::aid-anie4588>3.0.co;2-5
|View full text |Cite
|
Sign up to set email alerts
|

Bis(pentafluorophenyl)xenon, Xe(C6F5)2: A Homoleptic Diorganoxenon Derivative

Abstract: A step forward in organo xenon chemistry: The fluoride‐initiated reaction of Me3SiC6F5 and XeF2 leads, via the intermediate C6F5XeF, to an isolable [10‐Xe‐2] species with two xenon–carbon bonds (see scheme).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

2001
2001
2012
2012

Publication Types

Select...
6
3

Relationship

2
7

Authors

Journals

citations
Cited by 42 publications
(5 citation statements)
references
References 31 publications
(3 reference statements)
0
5
0
Order By: Relevance
“…The group of Professor Frohn at the University of Duisburg, Germany, synthesized fnrst CeFsXeF from CeFsXe* salts and N(CH3)4F by metathesis and then converted it to CeFsXeCeFs and CsFsXeCN by reacting it with Cd(C6F5)2 and (CH3)3SiCN, respectively [4]. In a different approach, the group of Professor Naumann at the University of Koeln, Germany, found that CeFsXeCeFs and CeFsXeF are directly accessible from XeFa and (CH3)3SiC6F5 [5]. and Xe-Cl bonds [6].…”
Section: Karl O Christe"mentioning
confidence: 99%
See 1 more Smart Citation
“…The group of Professor Frohn at the University of Duisburg, Germany, synthesized fnrst CeFsXeF from CeFsXe* salts and N(CH3)4F by metathesis and then converted it to CeFsXeCeFs and CsFsXeCN by reacting it with Cd(C6F5)2 and (CH3)3SiCN, respectively [4]. In a different approach, the group of Professor Naumann at the University of Koeln, Germany, found that CeFsXeCeFs and CeFsXeF are directly accessible from XeFa and (CH3)3SiC6F5 [5]. and Xe-Cl bonds [6].…”
Section: Karl O Christe"mentioning
confidence: 99%
“…These compounds are remarkable because they involve, by analogy with XeF2, semi-ionic 3-center/4-electron bonds [7][8][9] that are only half as strong as the previously known predominantly covalent Xe-C and Xe-Cl bonds in the [XeCeFs]* [10,11] and [XeCl]^ [6] cations, respectively. Although the synthesis of CFsXeCFs hac^een claimed ^eady) in 1979 [12], all attempts to verify this claim have failed so far [5].…”
Section: Karl O Christe"mentioning
confidence: 99%
“…12 Thus, the typical products of that type of organic rare gas chemistry were fully fluorinated, as C 6 F 5 -Xe-C 6 F 5 . 13 The reactions used to obtain these compounds were carried out in organic solvents, such as CH 2 Cl 2 , at temperatures not far from room temperatures.…”
Section: Introductionmentioning
confidence: 99%
“…5 Recently the neutral polyfluorophenyl xenon(II) molecules of the type ArXeF, Ar 2 Xe, and ArXeArA were prepared. 6,7,8 The current research in Xe-C chemistry is compiled in some reviews. 9 In In 1999 we elaborated a convenient route to arylxenon(II) tetrafluoroborates which consists of the reaction of aryldifluoroborane with xenon difluoride in CH 2 Cl 2 at 240 to 230 °C.…”
mentioning
confidence: 99%